The mosquitoes (Diptera: Culidae) of Seychelles: taxonomy, ecology, vectorial importance, and identification keys - Le Goff, Gilbert (BioMed Central, 2012)
BACKGROUND: During recent periods, the islands of the Republic of Seychelles experienced many diseases such as dengue, chikungunya, Bancroft’s filaria and malaria. Mosquitoes transmit the agents that cause these diseases. Published information on mosquitoes in the Seychelles is notably dispersed in the literature. The maximum number of species obtained on a single field survey does not exceed 14 species. METHODS: We performed a comprehensive bibliographic review using mosquito and Seychelles as the key words, as well as conducted a mosquito field survey for larval and adult stages during the rainy season in December 2008. Sixteen sites were sampled on four granitic islands (Mahé, Praslin, La Digue and Aride) and six sites on coralline atolls in the extreme southwest of the country (Aldabra group). RESULTS: We found published references to 21 mosquito species identified at least on one occasion in the Seychelles. Our collections comprised 18 species of mosquitoes, all of them from the subfamily Culicinae; no Anophelinae was found. We also confirm that Aedes seychellensis is a junior synonym of Ae. (Aedimorphus) albocephalus. The first records for Culex antennatus and Cx. sunyaniensis are presented from the country, specifically from Aldabra and Praslin, respectively. Based on a comparison of the taxa occurring on the granitic versus coralline islands, only three species, Ae. albocephalus, Cx. scottii and Cx. simpsoni are shared. Aedes albopictus appeared to exclude largely Ae. aegypti on the granitic islands; however, Ae. aegypti was common on Aldabra, where Ae. albopictus has not been recorded. The notable aggressiveness of mosquitoes towards humans on coralline islands was mainly due to two species, the females of which are difficult to distinguish: Ae. fryeri and Ae. (Aedimorphus) sp. A. The number of mosquito species collected at least once in the Seychelles is now 22, among which five species (Ae. (Adm) sp. A, Cx. stellatus, Uranotaenia browni. Ur. nepenthes and Ur. pandani) and one subspecies (Ae. vigilax vansomerenae) are considered as endemic. Two illustrated identification keys, one for adult females and the other for larval stages, are presented. CONCLUSIONS: The knowledge of the culicidian fauna in the Seychelles has been notably updated. The number of mosquito species is relatively large with regards to land surface and distances to continental Africa, although the anophelines are totally lacking. The complex natural history of mosquitoes in the Seychelles provides examples of both vicariance- and dispersal-mediated divergences. They present superb examples for theoretical and applied island biology.